Characterisation of the Plasmodium falciparum ER-localised Hsp90-Hsp110 chaperone complex - Stofberg, Melissa Louise (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.